2016
DOI: 10.1038/nchembio.2229
|View full text |Cite
|
Sign up to set email alerts
|

DPP8 and DPP9 inhibition induces pro-caspase-1-dependent monocyte and macrophage pyroptosis

Abstract: Val-boroPro (talabostat, PT-100), a nonselective inhibitor of post-proline cleaving serine proteases, stimulates mammalian immune systems through an unknown mechanism of action. Despite this lack of mechanistic understanding, Val-boroPro has attracted significant interest as a potential anticancer agent, reaching Phase III trials in humans. Here we show that Val-boroPro stimulates the immune system by triggering a proinflammatory form of cell death in monocytes and macrophages known as pyroptosis. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
252
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(282 citation statements)
references
References 46 publications
17
252
1
2
Order By: Relevance
“…Similar to the results in RAW 264.7 macrophages, we observed that Val-boroPro treatment of GSDMD −/− THP-1 cells (Okondo, et al, 2017), but not control or CASP1 −/− cells, induced PARP cleavage (Fig. 2A, Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to the results in RAW 264.7 macrophages, we observed that Val-boroPro treatment of GSDMD −/− THP-1 cells (Okondo, et al, 2017), but not control or CASP1 −/− cells, induced PARP cleavage (Fig. 2A, Fig.…”
Section: Resultssupporting
confidence: 88%
“…We previously showed that knockout of GSDMD delayed, but did not entirely prevent, DPP8/9 inhibitor-induced cell death in human THP-1 macrophages (Okondo, et al, 2017). To confirm that Gsdmd is similarly not essential for DPP8/9 inhibitor-induced cell death in mouse macrophages, we generated several Gsdmd −/− RAW 264.7 macrophage cell lines using CRISPR/Cas9 gene editing technology (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…60 PAPA syndrome is caused by heterozygous mutations in PSTPIP1 and although it is understood that the inflammatory manifestations in PAPA syndrome are pyrin dependent, 61,62 the exact mechanism of disease is unclear. [66][67][68][69] An autosomal recessive form of generalised pustular psoriasis has also been described. 63 Two rare dermatological conditions, multiple selfhealing palmoplantar carcinoma and familial keratosis lichenoides chronica, have recently been linked to activating heterozygous mutations in NLRP1.…”
Section: Dermatological Presentationmentioning
confidence: 99%